2011
DOI: 10.1007/s12975-011-0095-z
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Delivery of Stem Cells

Abstract: The method of delivery of stem cells is a major factor to consider in the design of clinical trials of cell therapy. Different methods of delivery will be associated with different risks to the patient, and may also be associated with different potential for benefit. Current approaches are partly informed by the routes selected for study in animal models of focal ischaemia and CNS transplantation, but there has been little work comparing the efficacy of different routes of administration. Direct intraparenchym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 43 publications
2
10
0
Order By: Relevance
“…The experience in trials of cell implantation for Huntington's or Parkinson's diseases, as well as stroke, includes cell injections targeted to the basal ganglia of 0·5 up to 10 million cells in volumes of 10–200 μl. In a review, 12/238 adverse events related to surgery were reported, consistent in character with a wider literature on stereotaxic surgery that indicates risks of around 1·7% for intracranial bleeding, mostly subdural hemorrhage, and seizures, with an overall mortality of 0·3% and morbidity of 1·4% .…”
Section: Clinical Issuessupporting
confidence: 58%
“…The experience in trials of cell implantation for Huntington's or Parkinson's diseases, as well as stroke, includes cell injections targeted to the basal ganglia of 0·5 up to 10 million cells in volumes of 10–200 μl. In a review, 12/238 adverse events related to surgery were reported, consistent in character with a wider literature on stereotaxic surgery that indicates risks of around 1·7% for intracranial bleeding, mostly subdural hemorrhage, and seizures, with an overall mortality of 0·3% and morbidity of 1·4% .…”
Section: Clinical Issuessupporting
confidence: 58%
“…There were no cell-related adverse events. Serious adverse events (SAEs) related to the procedure were noted from imaging in 4 out of 11 patients, but none were symptomatic, a finding consistent with general safety data for brain stereotactic procedures [103,104]. No incidence of seizures was recorded, unlike previous trials in which teratocarcinoma-derived neuronal cells [105,106] and fetal porcine cells [107] were implanted to treat stroke.…”
Section: Recent Clinical Experiencesupporting
confidence: 68%
“…While this is certainly an important consideration for any method of opening the BBB, the targeted and transient nature of this FUS-induced BBBO greatly minimizes the risk of adverse exposure, especially compared to more invasive and less targeted approaches (e.g. intracranial injection (Muir et al, 2011) and mannitol-induced BBBO (Nagy et al, 1979)). Additionally, the ability to open the BBB in a targeted manner restricts potentially negative exposures to the affected regions of the brain.…”
Section: Safety Of Focused Ultrasound and Microbubble Mediated Blomentioning
confidence: 99%